Working capital management: evidence from Malaysian ICT industry / Wahida Ahmad and Rozihanim Shekh Zain - Ahmad, Wahida; Shekh Zain, Rozihanim (Universiti Teknologi MARA, Perlis, 2017)
Previous studies dedicate their knowledge in working capital management. This paper provides useful insights on the determinants of working capital management in Malaysian ICT industry. Efficient working capital management is vital to ensure companies liquidity and ensuring its sustainability The objective of this study is to examine working capital’s influence on profitability, leverage, operating cash flow, and non-debt tax shield. Using unbalanced panel data, the study employs random effects model for 634 observations. The study covers a ten (10) years period from 2004 to 2013 of 104 publicly listed ICT companies in Malaysia. The study have shown significant relationship between all determinants and working capital ratio. Leverage, cash flow, and non-debt tax shield is negatively related with working capital while profitability is positively related with working capital. The interaction effects disclose cash flow and leverage have a different impact on working capital for small and large ICT companies in Malaysia.